The Neolithic site “La Marmotta”: DNA metabarcoding to identify the microbial deterioration of waterlogged archeological wood - Beccaccioli, Marzia; Moricca, Claudia; Faino, Luigi; Reale, Rita; Mineo, Mario; Reverberi, Massimo (Frontiers in Microbiology, 2023)
The evaluation of biological degradation of waterlogged archaeological wood is crucial to choose the conservative and protective treatments to be applied to the wooden material. The waterlogged environmental conditions are characterized by oxygen scarcity, only allowing the growth of adapted microbes capable to degrade the organic wooden material, mainly erosion bacteria and soft-rot fungi. In this work, we characterized and evaluated the biodegradation state and the microbial communities of wooden fragments preserved in storage tanks. These were preserved by waterlogging within the Neolithic village "La Marmotta", currently found under the Bracciano Lake (Lazio, Italy). The waterlogged wood samples were first identified taxonomically with an optical microscope, also allowing an evaluation of their preservation state. The microbial community was then evaluated through the sequencing of Internal Transcribed Spacer sequences for fungi and 16S for bacteria with the Oxford Nanopore Technologies (ONT) MinION platform. The identified microbial community appears to be consistent with the waterlogged samples as many bacteria attributable to the erosion of wood and ligninolytic fungi have been sequenced. Moreover, the reported results, highlight the first use of targeted metabarcoding by ONT applied to study the biodeterioration of waterlogged archeological wood.